ANALYSIS OF THE MAIN CHARACTERS OF âTHE LORD OF THE RING- THE RETURN OF THE KINGâ A NOVEL BY J.R.R TOLKIEN - -, Ermalina; Rahayu, Pipit; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
Purpose of this research was to analyze the main characters in the novel âthe Lord of the Ring-the Return of the Kingâ and to know the characterization of main characters in the novel. In collecting the data, the researcher used observational method. In analyzing the data, the researcher used formalist criticism based on Guerin (1992). The result of the analysis is: there are five main characters that exist on the novel âthe Lord of the Ring-the Return of the Kingâ. They are Frodo, Aragon, Sam, Gandalf and Gollum and the characterizations of main characters are protagonist, antagonist, static and dynamic